PENGARUH KUALITAS JURUSAN TERHADAP KEPUASAN MAHASISWA SERTA DAMPAKNYA PADA LOYALITAS MAHASISWA BARU TAHUN AJARAN 2017 – 2018 PADA JURUSAN MANAJEMEN DAKWAH UNIVERSITAS ISLAM NEGERI AR-RANIRY BANDA ACEH - Cut devi maulidasari; Riznal Ahkyar (universitas teuku umar, 2018)
ABSTRACTThe purpose of this study was to determine the influence of the quality of majors on student satisfaction and their impact on the loyalty of students of the Department of Da'wah Management at the State Islamic University Ar-Raniry Banda Aceh. Data analysis is the process of simplifying data into a form that is easier to read and implement. The method chosen to analyze the data must be in accordance with the research pattern and the variables to be studied. This research uses Structural Equation Modeling (SEM) method with research tools or software in the form of Partial Least Square (PLS). From the research that has been done through observation and secondary data, it can be concluded that the quality of the department, student satisfaction and the loyalty of students of the Da'wah Management Department of the Ar-Raniry State Islamic University in Banda Aceh are still good. From the research that has been done, it can be concluded that the quality of the department affects student satisfaction, with a t statistic value of 15,639. Furthermore, from the results of the tests that have been carried out, it can be concluded that the quality of the department affects the loyalty of students with a t statistic value of 14,319. From the research that has been done, it can be concluded that student satisfaction affects student loyalty, with a t statistic value of 22,281. And finally From the results of the research that has been done it can be concluded that the hypothesis which states that the quality of majors affects student loyalty through student satisfaction with a statistical value of 4,555. Keywords: quality, satisfaction and loyalty